On the Propagation of Vertical Acoustic Waves in the Solar Chromosphere - Mohammad Golmohammadian; Zanyar Ebrahimi (Iranian Journal of Astronomy and Astrophysics)
Sound waves have the potential to transfer the energy needed to heat the sun's atmosphere from the lower layers to higher areas. The source of these waves can be the surface oscillations of the sun, the most famous of which are the 5-minute oscillations. In this research, we investigate the propagation of sound waves in the first 2000 km of the sun's atmosphere, which is known as the chromosphere. In the chromosphere, variations in plasma density, hydrodynamic pressure, and temperature with height cause wave propagation to be complicated. Here, we build a chromospheric model using observational data and investigate sound propagation in both pulse and wave train modes. We solve the equation of motion numerically in the linear regime using the finite difference method. The results show that due to the reflection of the wave in different layers of the atmosphere, the sound pulse does not maintain its original shape, instead, its energy is spread in a wide space of the atmosphere. Also, for sinusoidal wave trains at different frequencies, we obtain the amount of the energy of the wave penetrating to the upper layers. Results show that as the frequency of the wave increases, the capability of the wave to transfer the acoustic energy from the photosphere to the upper chromosphere increases.